Efektivitas Kelincahan dan Kecepatan dengan Kemampuan Menggirng Pada Permaian Sepak Bola - Roni Effendi, Awang; Suhairi, Muhammad; Rustanto, Heri; Suramli4, Suramli (Indonesian Journal of Physical Education and Sport Science, 2022)
This study aims to determine the effectiveness of the relationship between agility, speed and dribbling ability. This research is multiple correlational with the independent variables in this study are agility (X1) and speed (X2) and the dependent variable is the ability to dribble (Y). The population in this study were students who took part in the extracurricular activities of State Junior High School 2 Sungai Raya totaling 42 students with the total sample being taken using a total sampling technique. To measure agility using an agility run test and for a speed test using a 60-meter run, while to measure the ability to dribble the ball is taken based on skills, namely running while dribbling the ball through cones. This research was carried out in the courtyard of the State Junior High School 2 Sungai Raya in November 2021. The results revealed that there was a significant relationship between agility (X1) and the ability to dribble a soccer game (Y). The correlation coefficient rx1y = 0.506. rtabel = 0.308 with n = 42 at a significant level of 5%. There is a significant relationship between speed (X2) and the ability to dribble a soccer game (Y), the correlation coefficient is rx2y = 0.435. If tested the significance with rtabel = 0.308 with n = 42 at a significant level of 5%. There is a significant relationship between agility and speed with the ability to dribble soccer games in extracurricular male students at State Junior High School 2 Sungai Raya with a moderate level of correlation.